2017
DOI: 10.3389/fpls.2017.00712
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Genotype × Environment Interaction, Correlation, and GGE Biplot Analysis for Grain Iron and Zinc Concentration and Other Agronomic Traits in RIL Population of Sorghum (Sorghum bicolor L. Moench)

Abstract: The low grain iron and zinc densities are well documented problems in food crops, affecting crop nutritional quality especially in cereals. Sorghum is a major source of energy and micronutrients for majority of population in Africa and central India. Understanding genetic variation, genotype × environment interaction and association between these traits is critical for development of improved cultivars with high iron and zinc. A total of 336 sorghum RILs (Recombinant Inbred Lines) were evaluated for grain iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 64 publications
(80 reference statements)
17
60
0
1
Order By: Relevance
“…There is no biological reason for the division into these specific mega-environments. Similarly, as in the case of the sugar beet [28,29], the lack of justification for the division of locations into a mega-environment was observed in many other species of arable crops [30,31].…”
Section: Discussionmentioning
confidence: 85%
“…There is no biological reason for the division into these specific mega-environments. Similarly, as in the case of the sugar beet [28,29], the lack of justification for the division of locations into a mega-environment was observed in many other species of arable crops [30,31].…”
Section: Discussionmentioning
confidence: 85%
“…Grain Fe and Zn content in several crops including sorghum (Upadhyaya et al, 2016;Phuke et al, 2017), pearl millet (Kanatti et al, 2014), proso millet (Vetriventhan and Upadhyaya, 2018), and finger millet (Upadhyaya et al, 2011a) were significantly and positively correlated. However, in this study, Fe and Zn content showed significant correlation only in 2016, indicating that the performance of accessions between years and consequently the correlation between the traits, differ mainly due to the influence of year (environments) and genotype ´ year interaction.…”
Section: Discussionmentioning
confidence: 97%
“…Average Zn (23-25 mg kg −1 ) and protein (7.9-8.5%) contents in the kodo millet accessions used in this study were greater than those in finger millet germplasm (Zn 19.9 mg kg −1 , protein 7.3%) (Upadhyaya et al, 2011a), and Ca content (190-213 mg kg −1 ) was greater than in foxtail millet (146 mg kg −1 ) (Upadhyaya et al, 2011b) and proso millet (165 mg kg −1 ) (Vetriventhan Table 7. High genotype ´ environment interaction has been reported for grain nutrient content in several crops including maize (Oikeh et al, 2004), sorghum (Phuke et al, 2017), pearl millet (Pucher et al, 2014), and affects the rank of genotypes across environments. (Ward, 1963).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, all traits were found highly heritable except days to emergence, root length, and secondary branches as per scale of Robinson [39] ( Table 2). The magnitude of heritability is mainly governed by the level of genetic variability, while higher heritability results in lower environmental effects on a specific trait [40]. Analysis of variance (ANOVA) for most of studied traits reflected that genotypic variances were highly significant within as well as across the environment, revealing their higher level of heritability.…”
Section: Discussionmentioning
confidence: 99%